Affordable innovation facilitating renewable energy deployment: Two ‘smart’ energy poverty alleviation case examples - Ronald Beckett (Journal of Innovation Management, 2023)
This paper considers one aspect of UN Sustainable Development Goal SDG7 - the intention to \textquotesingle leave no-one behind\textquotesingle{} in the transition to renewable energy. The target beneficiaries have access to affordable electricity restricted in some way. Two examples of affordable innovation based on artificial intelligence-driven microgrid technology serving clients in developing and developed economies are presented. These initiatives provide direct economic, environmental and social benefits, but also add to the quantum of renewable energy generated in their local areas. A multiplicity of community, enterprise and government actors cooperate in establishing and operating the particular programs described, and community benefits extend beyond simple economic outcomes, e.g., building social capital and trust in the technology. A model characterizing a broader view of SDG 7 realization dynamics is presented. This includes the identification of four kinds of learning space and the notion of tipping points, which may be topics for further research.